Wewnętrzna komunikacja jako zakres oddziaływania public relations - cele, zasady, znaczenie, narzędzia - Kulig-Moskwa, Katarzyna (Internal communication as an area of PR influence - aims, rules, meaning tools, 2007)
The article describes the role of intemal PR for organization. It presents the main aims, mistakes, principles, and instruments of correct intemal communication in organizations. The importance of intemal PR will grow in the futurę.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 151-159